PENGARUH STRATEGI INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD SUBSIDI SWAKARYA T.A. 2020/2021 - Akden Simanihuruk; Lidia Simanihuruk; Miftahul Jannah (Universitas Negeri Medan, 2021)
Abstract: The Influence of Inside Outside Circle Strategy On Student Learning on The Beautiful of My Country’s Diversity Theme at 4 Primary Class at Subsidi Swakarya T.A 2020/2021. The purpose of this study was to determine the effect of the Inside Outside Circle strategy on student learning outcomes on the theme The Beauty of Diversity in my Country, grade IV SD Subsidi Swakarya T.A. 2020/2021. The population of this study was all 121 students of grade VI SD Subsidi Swakarya. Samples were taken randomly as many as 40 people, 20 people for the experimental class and 20 people for the control class. This type of research is experimental research. The instrument used in this research is a multiple choice test. The average value of the experimental class is 77.25. As for the control class is 66.25. Thus, it can be said that the average value of student learning outcomes in the experimental class is higher than the control class. The data were analyzed by hypothesis testing using the